Sugarcane Landraces of Ethiopia: Germplasm Collection and Analysis of Regional Diversity and Distribution - Esayas Tena Gashaw; Firew Mekbib; Amsalu Ayana (Advances in Agriculture)
Sugarcane has been cultivated by smallholder farmers since 16th century in Ethiopia and preceded the commercial production. However, as far as this study is concerned, no exploration and collection have been conducted to know the landraces and study the regional diversity of the crop. Therefore, the objectives of this study were to collect native sugarcane landraces in Ethiopia and to assess phenotypic diversity and analyze regional distribution among landraces collected from different geographical regions. More than 300 sugarcane genotypes were collected. The landraces were analyzed for 21 quantitative stalk and juice quality characters and 16 qualitative characters. Phenotypic diversity among landraces was high, as expressed by the large range of variation for mean quantitative traits and the high (0.80) Shannon–Weaver diversity index. Our results provided experimental evidence on occurrence of geographical variation and significant within-region variation where it was high in the regions of Amhara, Benshangul-Gumz, and SNNPR. Wide variability of agronomically important characters in sugarcane such as millable stalk count at harvest, single cane weight, and plant height was observed among regions. These characters also demonstrated high correlation with cane and sugar yield and the altitude of the collection sites. Therefore breeders can utilize accessions of regions showing variability for these characters in selection programs and to design breeding strategies to produce varieties with best commercial merits. The present study contributes to updating sugarcane descriptors adopted from USDA-ARS as well as Bioversity passport data for the future collection and evaluation. The paper discussed insinuation of the results with regard to plant breeding, germplasm collection, and conservation as well as the plausible sources for the wide range of variation observed. This is the first study to report landrace sugarcane genetic resources in Ethiopia and information on geographical pattern of variation in Ethiopian local sugarcane germplasm.